Pelatihan Media Powerpoint Slide Master Berbasis Pembelajaran Kolaboratif Di Sma Kelurahan Bukit Lama Palembang - Amrina, Dian Eka; Jaenudin, Riswan; Fatimah, Siti; Mardetini, Edutivia (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2019)
The teacher in Bukit Lama Village, Ilir Timur 1 Sub-district, Palembang has been accustomed to using powerpoint media as a tool to implement the Social Sciences learning. However, in its utilization the teacher only describes learning material on powerpoint slides. Teachers cannot yet create master slides for their learning material in an integrated manner by implementing collaborative learning. The purpose of this service is to provide knowledge and to improve teacher skills to create and use powerpoint slide master learning media based on collaborative learning. This service was carried out in Srijaya State High School Palembang, with a target audience of 30 Private High School teachers in Bukit Lama village consisting of Srijaya Negara High School, PGRI 1 High School and Taruna Bangsa High School. The service model used is a model of mentoring with technical assistance methods in making powerpoint slide master learning media based on collaborative learning. Evaluation of activities is carried out by product testing and product assessment. The initial knowledge test results regarding the powerpoint slide master media based on collaborative learning are an average of 7.04, increasing to an average of 8.96 in the final knowledge test. Improved test results by 0.43 in the medium category. Product assessments made by the target audience indicate that the products made are in good category with a value of 77.42%. In conclusion, this dedication activity can provide knowledge and skills for the target audience in making powerpoint slide master learning media based on collaborative learning.